1981
DOI: 10.1111/j.1467-9450.1981.tb00392.x
|View full text |Cite
|
Sign up to set email alerts
|

On intelligence II: A neo‐Spearman model to replace Cattell's theory of fluid and crystallized intelligence

Abstract: o r w a yUndheim, J. 0.: On intelligence 11: A neo-Spearman model to replace Cattell's theory of fluid and crystallized intelligence. Scandinavian journal of Psychology, 1981,22, 181-187. While many empirical studies now support second-order simple structure factor analytic distinctions consistent with Cattell's theory of fluid and crystallized intelligence, the hierarchical order analyses carried out in the present study show that these factors are structured so as to suggest a neo-Spearman hierarchical model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The equality of g and Gf also has been demonstrated empirically in a series of studies in which a higher-order g-factor has been shown to have a perfect relationship with the Gf-factor (e. g., Gustafsson, 1984Gustafsson, , 1988Gustafsson, , 1994Gustafsson, , 2002Undheim, 1981;Undheim & Gustafsson, 1987). Since Gf is identified in an invariant manner, it follows that g too is invariantly defined as an apex factor in the CHC model.…”
Section: 1mentioning
confidence: 80%
See 1 more Smart Citation
“…The equality of g and Gf also has been demonstrated empirically in a series of studies in which a higher-order g-factor has been shown to have a perfect relationship with the Gf-factor (e. g., Gustafsson, 1984Gustafsson, , 1988Gustafsson, , 1994Gustafsson, , 2002Undheim, 1981;Undheim & Gustafsson, 1987). Since Gf is identified in an invariant manner, it follows that g too is invariantly defined as an apex factor in the CHC model.…”
Section: 1mentioning
confidence: 80%
“…The question about non-invariance of the g-factor has been approached in yet another way, which may be regarded as an extension of Spearman's theoretically based approach to the identification of g. Undheim (1981) and Gustafsson (1984) argued that the characteristics of the g-factor as described by Spearman (1904Spearman ( , 1927 agree so well with the characteristics of the Gf-factor as described by Horn & Cattell (1966), that g and Gf should be considered to be one and the same factor. The equality of g and Gf also has been demonstrated empirically in a series of studies in which a higher-order g-factor has been shown to have a perfect relationship with the Gf-factor (e. g., Gustafsson, 1984Gustafsson, , 1988Gustafsson, , 1994Gustafsson, , 2002Undheim, 1981;Undheim & Gustafsson, 1987).…”
Section: 1mentioning
confidence: 99%
“…Probably as a result of these complications, some have suggested (e.g., Gustafsson, 1984;Undheim, 1981) that Cattell's crystallized intelligence is equivalent to Vernon's v:ed factor. This study, however, makes clear that this is not the case.…”
Section: Complications In Distinguishing Between Modelsmentioning
confidence: 97%
“…Only Guilford (1956), of the major psychometric intelligence theorists, fails to be included (Gustafsson, 1984). Thus, whether one examines the analyses of diverse mental test batteries given to large, discrete samples of participants (Bickley, Keith, & Wol e, 1995;Carretta & Ree, 1995;Gustafsson, 1984;Undheim, 1981aUndheim, , 1981b, or considers Carroll's (1993) standardized reanalyses of hundreds of mental test data sets gathered throughout the 20th century, the result is similar: human mental ability differences show near universal positive correlations; the packets of covariance in a heterogeneous mental test battery given to a broad sample of adults or children can be arranged into correlated group factors; and a g factor can be extracted that accounts for around 50% of the variance among individuals. Gustafsson referred to 'this unifying model' of mental abilities (p. 193) and summarized its characteristics as follows:…”
Section: The Structure Of Human Intelligence Differencesmentioning
confidence: 99%